A human capital measurement scale. Issue 2 (10th April 2017) - Vidotto, Juarez Domingos Frasson; Ferenhof, Helio Aisenberg; Selig, Paulo Mauricio; Bastos, Rogerio Cid
Abstract : Purpose: Despite the large number of academic publications in human capital, there are few instruments to measure it. The purpose of this paper is to develop a holistic scale to measure human capital, considering aspects related to competence, attitudes, skills, leadership, and organizational memory. Design/methodology/approach: First, a literature review of the existing measurement models was carried out. Second, based on the results the authors developed a scale and a questionnaire that were applied in a financial institution in Santa Catarina, Brazil, supported by a factor analysis and a reliability analysis. Findings: As a result of this study a scale consisting of 13 variables of human capital emerged that have been grouped into three factors – leadership and motivation; qualifications; and satisfaction and creativity – which can assist in the organization's human capital measurement. From a theoretical view, a more holistic scale is provided, which helps to overcome a unilateral focus on knowledge (intangibles). Research limitations/implications: This work points out that the survey data were collected from a sample of 220 relationship managers of a specific financial institution. The results should be tested in other banks or organizations from other sectors to check their suitability and to be generalized. Practical implications: From a practical point of view, it contributes a "tool" that can assist in the measurement of human capital and in the knowledge contained, dimensioning the organizational memory and human repositories. Originality/value: This is the first study that provides a scale to measure organizational human capital from the Brazilian financial perspective.